Outlander : Go Tell the Bees That I Am Gone - Book 9 - Gabaldon, Diana (New York : Delacorte Press, 2021)
"It is 1779 and Claire and Jamie are at last reunited with their daughter, Brianna, her husband, Roger, and their children on Frasers Ridge. Having the family together is a dream the Frasers had thought impossible. Yet even in the North Carolina backcountry, the effects of war are being felt. Tensions in the Colonies are great and local feelings run hot enough to boil Hells teakettle. Jamie knows loyalties among his tenants are split and it wont be long until the war is on his doorstep"--
Keywords: North Carolina -- History -- Colonial period, ca. 1600-1775; Fiction; North Carolina -- History -- Revolution, 1775-1783; Fiction; Time-travel fiction; Historical fiction; Fantasy fiction; Fiction